Spectrum of childhood obstructive uropathy in Ibadan, Nigeria (2019)
Background and Objectives: Obstructive uropathy (OU) is an important cause of morbidity and mortality in childhood with congenital OU being among the top three aetiologies of paediatric end-stage kidney disease (ESKD). With paucity of data on the impact of childhood OU in a setting of largely unaffordable facilities for ESKD management, further studies are needed. The aim of the study was to appraise the aetiological pattern and short- term outcome of childhood OU. Methods: A descriptive cross-sectional study was conducted on consecutively presenting children aged 15 years and below with features of urinary tract obstruction at the University College Hospital, Ibadan between January 2009 and December 2012. Their biodata, clinical presentation, aetiology, treatment, and short- term outcome were analysed in addition to the prevalence of OU in relation to other childhood renal disorders. Results: Eighty-six children aged one day to 15 years with a median age of 2.5 years and a modal age of 6 years were recruited over a 4-year period. The male to female ratio was 4.7:1. Congenital OU occurred in 81% of cases, with the lower urinary tract more frequently affected (78%). Posterior urethral valves (PUV) was the most common cause of OU (59.3%) followed by pelvi-ureteric junction (PUJ) obstruction in 17.4%; 73.3% of all PUJ obstructions occurred in females. Only 3.5% of cases were detected prenatally. Of all incident admissions into the Paediatric Nephrology Unit, OU accounted for 20.7%. An in-hospital mortality rate of 5% occurred. Conclusion: Childhood OU is a significant cause of renal disease in Ibadan accounting for one-fifth of new paediatric renal admissions. It was majorly congenital with a male preponderance and PUV was the most common cause. Contrary to expectations, PUJ obstruction occurred more often in females. Prenatal diagnosis rate was very low.